761 PRASUGREL OR CLOPIDOGREL IN PATIENTS WITH ACUTE CORONARY SYNDROMES AT DIFFERENT THROMBOTIC RISK: RESULTS FROM THE PROMETHEUS STUDY. (15th December 2022) - Chiarito, Mauro; Cao, Davide; Sartori, Samantha; Zhang, Zhongjie; Vogel, Birgit; Nicholas, Johny; Pivato, Carlo Andrea; Spirito, Alessandro; Tavenier, Annerieke; Effron, Mark; Stefanini, Giulio G; Baber, Usman; et al.
Abstract: Background: Potent P2Y12 inhibitors are recommended in patients with acute coronary syndrome (ACS), although the optimal antithrombotic strategy should be tailored based on patients thrombotic and hemorrhagic risk profile. We evaluated if the benefits associated with prasugrel vs. clopidogrel in ACS patients undergoing percutaneous coronary intervention (PCI) are similar in patients with different thrombotic risk profiles. Methods: PROMETHEUS was a multicenter observational study comparing prasugrel vs. clopidogrel in ACS patients undergoing PCI. Patients were defined at high thrombotic risk if presenting with a clinical and a procedural risk feature. The primary endpoint was major adverse cardiac events (MACE), composite of death, myocardial infarction, stroke, or unplanned revascularization. Hazard ratio (HR) and 95% confidence intervals (CI) were calculated using propensity-stratified analysis and with multivariable Cox regression. Results: Among 16, 065 patients, 4, 293 were defined at high and 11, 772 at low-to-moderate thrombotic risk. Patients receiving prasugrel had less comorbidities and risk factors than those treated with clopidogrel, both in the high and low-to-moderate thrombotic risk strata. High thrombotic risk patients had increased rates of ischemic and bleeding events at 90-day and 1-year follow-up. Patients treated with prasugrel had a lower adjusted 1-year risk of MACE (HR 0.86, 95% CI 0.77-0.96), irrespective of their thrombotic risk (pinteraction =0.32). Stratifying the study population by number of risk factors there was a significant interaction (pinteraction =0.026) for a greater reduction in MACE with prasugrel among patients with ≤1 thrombotic risk factor. The risk of clinically significant bleeding was similar in patients treated with prasugrel and clopidogrel. Conclusions: Patients with ACS at high thrombotic risk who undergo PCI are at increased risk of adverse events at 1 year. Prasugrel, mainly reserved to patients with less comorbidities, reduced the risk of ischemic events both in patients at high and low-to-moderate thrombotic risk as compared with clopidogrel.